2006
DOI: 10.1038/sj.mp.4001838
|View full text |Cite
|
Sign up to set email alerts
|

Depressive symptoms and insulin resistance in young adult males: results from the Northern Finland 1966 birth cohort

Abstract: The association between insulin resistance (IR) and depression is a subject of growing research interest, especially as previous population-based studies have presented conflicting findings. The present study extends our understanding about the putative impact of the severity of depressive symptoms on this association and it provides further epidemiological evidence in support of earlier findings, suggesting that the association between IR and depression is present already in young adult males. To determine th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
4

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(39 citation statements)
references
References 19 publications
0
35
4
Order By: Relevance
“…Each of these may contribute to the increased risk of dementia seen in patients with diabetes who are also depressed. Both depression and type 2 diabetes are also associated with signs of systemic inflammation 33, 34 , decreased insulin sensitivity 34, 35 , and autonomic dysfunction 36, 37 , which may mediate the effects of depression on dementia risk. Studies of the increased risk for mortality and repeat cardiac events in patients with depression following myocardial infarction have suggested that most of this effect is due to health behavior, specifically physical activity and medication adherence.…”
Section: Discussionmentioning
confidence: 99%
“…Each of these may contribute to the increased risk of dementia seen in patients with diabetes who are also depressed. Both depression and type 2 diabetes are also associated with signs of systemic inflammation 33, 34 , decreased insulin sensitivity 34, 35 , and autonomic dysfunction 36, 37 , which may mediate the effects of depression on dementia risk. Studies of the increased risk for mortality and repeat cardiac events in patients with depression following myocardial infarction have suggested that most of this effect is due to health behavior, specifically physical activity and medication adherence.…”
Section: Discussionmentioning
confidence: 99%
“…The association between depression and risk of IR was examined in 2,609 men from the Northern Finland 1966 birth cohort [8], and it was found that IR (QUICKI) was positively associated with current severe depression after controlling for body mass index. However, one of the limitations was the use of the Hopkins' Symptom Checklist-25 method, another selfreport measure of depression.…”
Section: Cross-sectional Studiesmentioning
confidence: 99%
“…Two cross-sectional studies were conducted by Timonen et al [8,9] in Finnish samples. The association between depression and risk of IR was examined in 2,609 men from the Northern Finland 1966 birth cohort [8], and it was found that IR (QUICKI) was positively associated with current severe depression after controlling for body mass index.…”
Section: Cross-sectional Studiesmentioning
confidence: 99%
“…65 Moreover, among young adult males in 2 Finnish population samples, severity of depressive symptoms was associated with insulin resistance. 66,67 In meta-analytic findings, depressive symptoms along with other psychological symptoms were more common among children with versus without T2DM, 68 and there was preliminary evidence that the association between depression and T2DM was especially strong in youth. 69 There is pharmacoepidemiological evidence of elevated rates of hyperglycemia and †"Youth" is used in this statement as an umbrella term for children, adolescents, and/or young adults (defined here as mean sample age within 1 standard deviation of 30 years).…”
Section: Insulin Resistance and Diabetes Mellitus (T2dm)mentioning
confidence: 99%